Jews and Christians in Denmark : from the Middle Ages to recent times circa 1100-1948 - Lausten, Martin Schwarz. (The Brill Reference Library of Judaism, 2015)
In Jews and Christians in Denmark: From the Middle Ages to Recent Times, circa 1100-1948 , Martin Schwarz Lausten investigates how the Church and society followed the European antijudaistic tradition using insults, adversities and attempted conversions during Catholic times from around 1100 and Protestant times starting around 1536. In spite of the tolerant policies of integration initiated by the government beginning in the 1800's, anti-Semitic movements arose among priests, professors and local authorities. However, during the German occupation (1940-1945) priests and many others assisted the 7,000 Danish Jews in their escape to Sweden. Based on Jewish and Christian sources, Jewish reactions to life in Denmark are also examined.